2005
DOI: 10.1007/s10763-004-2975-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a K–5 Mathematics Program Which Integrates Children’s Literature: Classroom Environment and Attitudes

Abstract: ABSTRACT. This article describes a one-year study of 120 fifth grade students whose teachers participated in a program entitled Project SMILE (Science and Mathematics Integrated with Literary Experiences). The purpose of the study was to determine the extent to which the classroom implementation of Project SMILE positively influenced the classroom environment and student attitudes toward reading, writing and mathematics. This was accomplished by, first, facilitating a series of professional development worksho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 15 publications
2
19
0
3
Order By: Relevance
“…In Brunei Darussalam, Majeed et al (2002) used an English-language version of the MCI among 1565 lowersecondary mathematics students in 81 classes in 15 government schools and reported sex differences in classroom climate perceptions and associations between students' satisfaction and the classroom environment. In a small-scale evaluation of a K-5 program that integrates mathematics and children's literature, Mink and Fraser (2005) used the MCI in Florida and found congruence between students' actual and preferred classroom climate. In Texas, Scott Houston et al (2008) used the MCI in an evaluation of science kits among a sample of 588 grade 3-5 students.…”
Section: Instruments For Assessing Classroom Climatementioning
confidence: 99%
“…In Brunei Darussalam, Majeed et al (2002) used an English-language version of the MCI among 1565 lowersecondary mathematics students in 81 classes in 15 government schools and reported sex differences in classroom climate perceptions and associations between students' satisfaction and the classroom environment. In a small-scale evaluation of a K-5 program that integrates mathematics and children's literature, Mink and Fraser (2005) used the MCI in Florida and found congruence between students' actual and preferred classroom climate. In Texas, Scott Houston et al (2008) used the MCI in an evaluation of science kits among a sample of 588 grade 3-5 students.…”
Section: Instruments For Assessing Classroom Climatementioning
confidence: 99%
“…Students learn best when they are motivated (Murphy, ; Shatzer, ), and students who are exposed to mathematics‐related literature show more excitement for mathematics and put forth continued efforts (Clarke, ). In past studies, students have reported how much they like hearing stories in mathematics class and that they enjoy being able to relate their own experiences with something concrete like a school fair or car wash presented in a piece of literature (Jennings, ; Mink & Fraser, ). Students also self‐report that stories make mathematics easier to understand and more interesting to learn (Whitin & Whitin, ).…”
Section: How Might Geometry‐related Children's Literature Increase Stmentioning
confidence: 99%
“…Students also self‐report that stories make mathematics easier to understand and more interesting to learn (Whitin & Whitin, ). Furthermore, teachers note that literature sparks their students' interest and increases students’ confidence (Mink & Fraser, ). The use of literature makes students more engaged and more motivated to talk about what they are learning (Von Drasek, ).…”
Section: How Might Geometry‐related Children's Literature Increase Stmentioning
confidence: 99%
“…Project Creating Independence Through Student‐Owned Strategies (CRISS), a successful educational reform in Montana (Santa, 1996), was an attempt for school districts to change their focus from rote memorization to deep learning of content area subjects, including mathematics for secondary students by developing mathematical concepts through the use of reading, writing, listening, and discussing mathematical concepts. Mink and Fraser (2005) adapted Project CRISS for the elementary school level and renamed it Project Science and Mathematics Integrated with Literacy Experiences (SMILE). Through the implementation of Project SMILE in fifth‐grade mathematics classrooms studied, researchers were able to investigate the classroom environment and students' attitudes toward reading, writing, and mathematics by providing teachers with five professional development sessions and by asking teachers to implement what they learned in these sessions in their own mathematics classrooms.…”
mentioning
confidence: 99%
“…Proficiency in the area of literacy is critical in the understanding of all content areas, including mathematics. In fact, lack of literacy proficiency with mathematics‐related texts has been cited as a reason for poor performance in the area of mathematics (Mink & Fraser, 2005). Research indicated that in the area of mathematics, U.S. teachers were not proficient in integrating content areas, instead relying mostly on lecture, worksheets, and textbook problems to teach students mathematics (Hiebert et al., 2003; Wallace & Clark, 2005).…”
mentioning
confidence: 99%